2015
DOI: 10.3923/ijp.2015.672.680
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Evaluation and Antioxidant Potential of Garcinia indica Fruits on H2O2 Induced Oxidative Stress in THP-1 Cell Line

Abstract: Garcinia indica have been used for centuries with claim for its medicinal value by traditional practitioners to treat numerous diseases. The anti-oxidant activity of G. indica fruit which were assessed by determining the total phenolic content, evaluating the 2, 2-diphenyl-1-picrylhydrazyl, (DPPH) activity, superoxide dismutase (SOD) activity, as well as its ability to inhibit Nitric Oxide (NO) and also their effect on H 2 O 2 induced Reactive Oxygen Species (ROS) generation in human monocytic (THP-1) cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The antioxidant activities of the nano-preparations are presented as IC 50 values, which is the concentration of the extract that inhibits the formation of DPPH radicals by 50%, as indicated by the linear regression analysis. 28 ABTS radical-scavenging assay. The ABTS radical-scavenging assay was conducted by following the protocol of Re et al 29 The bluish-green ABTS [2,2 0 -azino-bis(3-ethyl benzothiazoline-6sulfonic acid)] radical was generated through the oxidation reaction resulting from mixing ABTS (7 mM) with potassium persulphate (2.45 mM).…”
Section: Characterization Of O-agnpsmentioning
confidence: 99%
“…The antioxidant activities of the nano-preparations are presented as IC 50 values, which is the concentration of the extract that inhibits the formation of DPPH radicals by 50%, as indicated by the linear regression analysis. 28 ABTS radical-scavenging assay. The ABTS radical-scavenging assay was conducted by following the protocol of Re et al 29 The bluish-green ABTS [2,2 0 -azino-bis(3-ethyl benzothiazoline-6sulfonic acid)] radical was generated through the oxidation reaction resulting from mixing ABTS (7 mM) with potassium persulphate (2.45 mM).…”
Section: Characterization Of O-agnpsmentioning
confidence: 99%
“…7,33 Leaf extracts of A. scholaris have high phenolic, flavonoid and carotene contents and exhibit potent in-vitro antioxidant functions by scavenging free radicals. 12,13 Pre-and post treatments of ethanolic leaf extracts of A. scholaris following APAP administration restored the TAS, TOS and TTH levels in hepatic tissue, whereas aqueous leaf extract treatment failed to restored these parameters. High hepatoprotective potential of ethanolic extract may be due to presence of high polyphenolic content in ethanolic leaf extract as compared to aqueous leaf extract of A. scholaris.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11] Polyphenolic compounds present in the leaf extract of A. scholaris exhibit potent in-vitro total antioxidant capacity and reducing power and also shown scavenging of free radicals like hydroxyl, peroxy and superoxide radicals. 12,13 These phytochemicals also have important role in stabilizing lipid peroxidation thus reduces cellular damage. Therefore, the present study was aimed to investigate the oxidative and histopathological alterations in liver induced by acetaminophen (APAP) toxicity in wistar rats and its protection by different leaf extracts of Alstonia scholaris Linn.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] (−)-Hydroxycitric acid [(−)-HCA] is the major active ingredient in the fruit rind of Garcinia cambogia. 16 A myriad of health effects have been attributed to (−)-HCA, such as inhibiting fatty acid synthesis, 12 reducing cholesterol content, 17 anti-inflammatory, 18 antioxidative, 19 antidiabetic 20 properties, and regulating gut microbiota 21 in animals and humans. It was found that (−)-HCA effectively inhibited fatty acid synthesis by inhibiting adenosine triphosphate (ATP)-citrate lyase, which blocked the conversion of citrate to acetyl CoA in the cytosol.…”
Section: Introductionmentioning
confidence: 99%